Relationships between Composition of Major Fatty Acids and Fat Distribution and Insulin Resistance in Japanese - Chikako Fujii; Toshihide Kawai; Koichiro Azuma; Yuko Oguma; Fuminori Katsukawa; Hiroshi Hirose; Kumiko Tanaka; Shu Meguro; Hideo Matsumoto; Hiroshi Itoh (Journal of Diabetes Research)
Objective. The aim of this study was to evaluate the relationships between the composition of free fatty acids (FFAs) and metabolic parameters, including body fat distribution, in Japanese. Methods. The study subjects were 111 Japanese patients (54 males, 57 females). Metabolic parameters and visceral and subcutaneous fat areas as determined by CT scanning at the umbilical level were measured. Glucose tolerance test (GTT) was performed by administering 75 g glucose orally. Results. The percentage of linoleic acid (C18:2), the greatest constituent among FFAs, was negatively correlated with visceral fat area (r=−0.411, p<0.0001), fasting glucose (r=−0.330, p<0.0001), HbA1c (r=−0.231, p=0.0146), and systolic blood pressure (r=−0.224, p=0.0184). Linoleic acid percentage was also significantly negatively correlated with HOMA-IR (r=−0.416, p<0.0001) by simple correlation. Based on the findings of OGTT, the 111 subjects were classified into three groups: 33 with normal glucose tolerance, 71 with impaired glucose tolerance (IGT), and 7 diabetic subjects. The percentage of serum linoleic acid in diabetic subjects was significantly lower than that in normal subjects. Conclusion. We conclude that serum linoleic acid level is negatively correlated with the accumulation of visceral fat in relation to a reduction of insulin resistance in Japanese subjects.